Proceeding of the 2nd Libyan Conference on Medical and Pharmaceutical Sciences - Atia, Ahmed (AlQalam Journal of Medical and Applied Sciences, 2018)
Speech of the Conference President “Dr. Ahmed Atia” It is my great pleasure to welcome you to the 2nd Libyan conference on Medical and Pharmaceutical Sciences held by the Research Scientific Center at University of Tripoli Alahlia. I would like to take this opportunity to express my profound gratitude to the founder of this university for supporting scientific enterprise. Our annually meeting has traditionally combined great scientific content with a tremendous opportunity to see and taste the diverse and beautiful flavors of research. This year an outstanding gallery of speakers from all over the country which exceeded 60 participants from different universities and research centres, will participate and share with us the most significant advances in our profession. Scientific research excellence is an essential principle for transforming human thinking and ways of life. Scientific discovery is a major driver of national prosperity, and social and economic sustainable development. For this reason we chose our theme for this 2nd Libyan conference “Excellence and Creativity in Scientific Research”. We support and provide care in all areas of research, we participate in a multitude of research activities, and enable modern high quality piece of research to be provided in a suitable, and proper manner. A unique and wonderful aspect of our 2018 meeting is that the conference committee has collaborated with the highest research center in Libya that is Biotechnology Research Center, Authority of Natural Science Research and Technology, and National Nanosciences & Nanotechnology Project. We have a great team working to make this a truly memorable meeting, and I look forward to meeting you annually.